INFLUENCE OF COPING STRATEGIES ON THE STUDENT’S WELL-BEING IN CONDITIONS OF DISTANCE LEARNING - Vavilova, Alyona (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article is devoted to the study of student's coping strategies influence on the level of their subjective well-being in conditions of distance learning. It was found that student's coping strategies have an impact on the level of their psychological comfort. Using regression analysis it was revealed that the variability of student's life well-being is determined by the following coping strategies: positive self-esteem; responsibility; planning; escape and self-control. It was developed the typology of students in the conditions of distance education, which includes such indicators of dominant coping strategies: the level of psychological comfort, dominant coping and measure of stress tolerance. According to the certain typology, three types of students were defined: 1) adaptive type (high indicators of well-being, high indicators of tolerance to stress, dominant strategies “self-esteem”, “responsibility” and “planning” ); 2) maladaptive type (low indicators of well-being, low indicators of tolerance to stress, dominant coping “escape”); 3) average adaptive type (average indicators of well-being, average indicators of tolerance to stress; dominant strategies “responsibility”, “self-control”, low indicators of coping “positive self-esteem”). The results of the study indicate that students who are best adapted to distance learning and have a high level of psychological comfort tend to evaluate themselves positively, treat work responsibly, plan their studies and have an average level of self-control.